Outcome of surgical resection of pelvic osteosarcoma - Puri, Ajay (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The aim of the following study is to evaluate the morbidity, oncologic results and functional outcome in nonmetastatic patients with primary osteosarcoma of the pelvis treated with surgical resection. MATERIALS AND METHODS: Twelve cases of nonmetastatic osteosarcoma of pelvis were operated as part of their multimodality treatment regime between November 2003 and May 2011. There were 5 males and 7 females with a median age of 22 years (range 8-39 years). Ten patients underwent limb sparing resections while 2 had a hindquarter amputation. All 10 cases of limb sparing surgery included resection of the acetabulum. A pseudarthrosis was carried out in 7 cases. Extracorporeal radiation therapy and reimplantation of the bone followed by fixation with plates was used in 1 case and an ischiofemoral arthrodesis was carried out in 2 cases. RESULTS: Surgical margins were free in 11 patients. Seven patients had a poor histological response to chemotherapy while 4 patients had a good response to chemotherapy. In the patient reconstructed with radiated auto bone graft, the histological response to chemotherapy could not be assessed. Surgery related complications were seen in 8 out of 12 patients (67%). Three of these patients (25%) required additional surgical intervention for their complications. All patients were available for followup. The median followup of survivors was 56 months (range 24-102 months). Four patients (33%) developed a local recurrence. At 5 years, overall survival was 67%. Patients with a good response to chemotherapy had a better overall survival when compared with patients with a poor response to chemotherapy. The mean Musculoskeletal Tumor Society functional score was 22 (range12-27). CONCLUSIONS: Though complex and challenging, surgery provides good local control and oncologic outcomes with acceptable function in patients with osteosarcoma of the pelvis treated with appropriate surgical resection as part of their multimodality treatment.